Research on the optimal scheme of 3E game for lightweight body-in-white under environmental protection policy. (August 2021) - Ding, Zhensen; Fang, Haifeng; Liu, Bin; Yao, Zhanhui; Liu, Jinzhou
Lightweight of body-in-white (BIW) can effectively achieve energy saving and emission reduction, is an important component of automobile lightweight, and how to ensure better economy while lightweight has attracted wide attention from industry and academia. This study deeply analyzed the stages of the full life cycle of internal combustion engine vehicle (ICEV) and battery electric vehicle (BEV), deconstructs the stages where the weight of BIW has a greater impact on the two, and introduces the concept of full-cycle closed-loop flow of materials to establish universal "Energy-Environment-Economy" Evaluation Model, also called 3E assessment model for auto components. In addition, the 3E-PSI model is established in combination with the PSI method, which further makes up for the shortcomings of the general 3E model that cannot select the optimal solution by considering energy consumption, emissions, and economy comprehensively. The 3E-PSI analysis of material lightweight of BIW is conducted, which takes the ICEV and BEV on the same platform as an example. The results show that in terms of energy consumption, the magnesium alloy BIW of the ICEV is the lowest, however, the aluminum alloy BIW of the BEV is the lowest. In terms of environmental emissions, magnesium alloy BIW is the lowest in both ICEV and BEV, which are 57% and 59.56% of ordinary mild steel BIW respectively; As far as economy is concerned, the ICEV have break-even points for all lightweight materials in the total mileage during lifetime, and the BEV only has a break-even point, that is, driving 78625.68 km, the cost of high-strength steel BIW is lower than ordinary low-carbon steel. In addition, the comprehensive optimal scheme of ICEV is BIW of magnesium alloy material, and the comprehensive optimal scheme of BEV is BIW of aluminum alloy material.